The Impact of Ambulance and Emergency Medical Services on Patient Survival and Clinical Outcomes: A Systematic Review (The Review of Diabetic Studies, 2025)
Emergency Medical Services (EMS) and ambulance systems are critical components of modern healthcare, providing rapid medical intervention and transportation for patients experiencing life-threatening conditions. This systematic review evaluates the impact of ambulance and pre-hospital emergency medical services on patient survival and clinical outcomes across various emergency conditions, including cardiac arrest, trauma, stroke, and respiratory emergencies. A systematic search was conducted in major databases including PubMed, Scopus, Web of Science, and Google Scholar for studies published between 2015 and 2025. Studies examining the relationship between EMS response time, pre-hospital interventions, and patient outcomes were included. The findings demonstrate that timely ambulance response, advanced life support interventions, and well-coordinated emergency medical systems significantly improve survival rates, reduce complications, and enhance overall clinical outcomes. Pre-hospital interventions such as cardiopulmonary resuscitation (CPR), defibrillation, airway management, and early hospital notification were identified as key determinants of improved patient prognosis. The review highlights the importance of strengthening EMS infrastructure, improving paramedic training, and integrating technology in pre-hospital care systems. These findings emphasize the essential role of ambulance services in reducing mortality and improving emergency healthcare delivery worldwide.